2011
DOI: 10.1007/s12155-011-9150-6
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of Jatropha curcas Resources and Identification of Population-Specific Markers

Abstract: Jatropha curcas L. is cited as one of the best candidates for future oil and biodiesel production. It is widespread in many tropical and subtropical countries but has not yet received much genetic improvement. The objective of this study was to collect Jatropha germplasm and characterize it with molecular markers. A total of 64 genotypes, collected from seven geographic locations on two continents, were analyzed with 32 simple sequence repeat and two candidate gene-specific primers (ISPJ-1 gene and Curcin-P2 g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 31 publications
2
12
0
Order By: Relevance
“…The two progenies from Cambodia (UFVJC 67 and UFVJC 68) that were evaluated were clustered with those from Brazil, which demonstrates that, in accordance with the results of Freitas et al (2011) and Biabani et al (2012), geographical diversity does not necessarily reflect genetic diversity. A similar result was obtained by Ricci et al (2012), who, working with J. curcas plants collected from different geographical regions (Brazil, Cape Verde, Cuba, Mozambique, and Senegal), reported the formation of two clusters, with one cluster composed of plants from Brazil, Mozambique, and Senegal and the other of plants from Cuba and Cape Verde. Our study revealed a range of possible crosses to be investigated in J. curcas.…”
supporting
confidence: 84%
“…The two progenies from Cambodia (UFVJC 67 and UFVJC 68) that were evaluated were clustered with those from Brazil, which demonstrates that, in accordance with the results of Freitas et al (2011) and Biabani et al (2012), geographical diversity does not necessarily reflect genetic diversity. A similar result was obtained by Ricci et al (2012), who, working with J. curcas plants collected from different geographical regions (Brazil, Cape Verde, Cuba, Mozambique, and Senegal), reported the formation of two clusters, with one cluster composed of plants from Brazil, Mozambique, and Senegal and the other of plants from Cuba and Cape Verde. Our study revealed a range of possible crosses to be investigated in J. curcas.…”
supporting
confidence: 84%
“…However, in the case of J. curcas, SSR-based studies have generally detected less diversity in Asian and South American germplasm (Basha et al, 2009;Rosado et al, 2010;Ricci et al, 2012) compared with those found with dominant markers. AFLP-based studies conducted with germplasm from the state of Chiapas, Mexico, and from Guatemala have detected the highest genetic diversity of this species, although questions remain about the structure and variation that can be detected with co-dominant markers.…”
Section: Introductionmentioning
confidence: 95%
“…Although there is a growing body of knowledge on the diversity of J. curcas , there remain two important informational gaps in the literature: (1) most reports focus on diversity of accessions or individuals (Basha and Sujatha 2007 ;Gupta et al 2008 ;Ranade et al 2008 ;Sun et al 2008 ;Abdulla et al 2009 ;Kumar et al 2009 ;Subramanyam et al 2009 ;Tatikonda et al 2009 ;Ikbal et al 2010 ;Pamidiamarri et al 2010 ;Shen et al 2010 ;Umamaheswari et al 2010 ;Wen et al 2010 ) , leaving out studies with a focus on populations, and (2) mostly Asian accessions have been studied, although to a lesser degree also South American (Hartmann-Neto et al 2006 ;Oliveira et al 2006 ;Rosado et al 2010 ) and African Ambrosi et al 2010 ;Ricci et al 2012 ) ; consequently, similar studies are needed in regard to Mesoamerican germplasm. Moreover, little attention has been paid to the study of phenotypic traits, such as the fatty acid composition of seeds and fl ower morphology, as markers to estimate genetic diversity.…”
Section: Introductionmentioning
confidence: 99%
“…Studies performed on germplasm collected in the Old World and South America have found low diversity and a narrow genetic base (Sun et al 2008 ;Popluechai et al 2009 ;Rosado et al 2010 ;Ricci et al 2012 ) . An understanding of the genetic diversity and population structure in the postulated center of diversi fi cation, Mesoamerica, will permit identi fi cation of genetic material useful for future improvement of the species.…”
Section: Introductionmentioning
confidence: 99%